Spot assessment of the marine invertebrate resources of Baybay waters - Germano, Bernardita P.; Guinocor, Gloriosa C. (Annals of Tropical Research, 1994)
The marine macrobenthic invertebrate resources of Baybay were assessed using the transect-quadrat method. Two samplings in 23 stations over an area of 2300 m² yielded a mean macroinvertebrate density of 117 individuals/100 m² A total of 142 invertebrate species belonging to 72 families in 16 classes in 7 phyla were identified. The three most dominant species are the barnacle Balanus sp. and the gastropods Nerita odonta and Clypeomorus bifasciata bifasciata. Gastropoda is the most dominant and most ubiquitous taxon. The commercially important genera Haliotis and Tridacna are also found in the area. Highest and lowest mean density were observed in Bunga and Kilim, respectively. Species diversity was highest in Plaridel and lowest in San Agustin. The mean species diversity of Baybay is lower than of the neighboring Cuatro Islas and Camotes Islands. Siltation appears to be a major macroinvertebrate density-controlling factor in Baybay waters. Thus, vigilance against slash-and-burn agriculture and the removal of rocks and boulders from major rivers should be increased. The pattern of diversity is probably imposed by bottom topography and the practice of beach seining. The trial mariculture of Haliotis and Tridacna in the southern stations is recommended to possibly increase local seed stocks of these species and introduce a potential source of alternative livelihood for small-scale fishermen. Further, it is recommended that some portion on beach-seined areas (stations from Baybay wharf to Marcos) be reserved for rehabilitation of vegetation so as to have a source of recruits for the exploited sites.